Comparative Analysis of Traditional Offline Classes And Online Learning: Enhancing Efficiency And Proving The Superiority Of Online Education - Dr. Hemachandran Ravikumar; Mohanraj Kumar; Dr Vasanthan G (Educational Administration: Theory and Practice, 2025)
Technological developments have greatly shaped the direction of education and resulted in a move from conventional offline classrooms to online learning. By assessing important elements including accessibility, flexibility, cost-effectiveness, student involvement, and general efficacy, this paper compares both learning environments. To evaluate their preferences and experiences with both instructional approaches, 100 school staff members, 300 students (from grades 6 through 12), and 100 parents/general public members answered a structured survey. Based on their controlled setting, direct instructor interaction, and greater discipline, the results show that 71% of school staff, 132 kids, and 34 parents choose conventional offline learning. 52 students and 7 parents, on the other hand, prefer online learning and point mostly to accessibility and flexibility. Of the parents (40 out of 100), a sizable fraction support a hybrid learning paradigm combining the advantages of online and offline schooling. The major issues raised by students and teachers are technical problems, a lack of student motivation, and less physical interaction, despite the advantages that online education presents. Only 20% of students in online learning feel their education to be completely engaging, so engagement rates in this form remain rather low. In parallel, 45% of students said online learning was "good," and 25% said it was "poor." Although teachers agreed that internet tools have increased their effectiveness in the classroom, some voiced worries about student discipline and classroom control. Parents noted that even while online learning saves time and money, it also causes more screen time and less social connection. The study comes to the conclusion that, in terms of engagement, discipline, and student-teacher connection, traditional offline education remains more effective even if online learning presents cost-effectiveness, flexibility, and greater accessibility. According to the study, the most efficient way to modernise education could be a hybrid learning model that combines the flexibility of digital platforms with organised offline instruction. Enhanced efficiency and general impact of online learning depend on further developments in its tactics, including better engagement techniques and interactive learning environments.